Pengaruh Penerapan Good Corporate Governance Terhadap Penghindaran Pajak pada Perusahaan di Indonesia - Mega Arisia Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of the implementation of good corporate governance on tax avoidance in companies in Indonesia. The mechanisms of good corporate governance in this study include managerial ownership, institutional ownership, independent board of commissioners, and accounting expertise background or audit finance committee. This study uses a sample of 48 companies listed on the Indonesia Stock Exchange, during 4 years of observation there were 192 annual reports analyzed. The sampling technique in this study was purposive sampling and the data analysis tool used in this study was multiple linear regression analysis. The results of this study are managerial ownership, institutional ownership, and independent board of commissioners do not affect tax avoidance. While the accounting or financial expertise background of the audit committee affects tax avoidance.